PERBEDAAN PENGARUH LATIHAN IMAGERY DAN TANPA LATIHAN IMAGERY TERHADAP PENINGKATAN KEMAMPUAN SHOOTING GAME ATLET PETANQUE UNDIKMA - Muhammad Ridwan Lubis; Andi Gilang Permadi (Jurnal Ilmiah Mandala Education (JIME), 2020)
This research is motivated by the inconsistency in the shooting ability of athletes in shooting game matches in the game of petanque sports both at the regional and national levels. This study aims to determine the effect of imagery training and concentration on improving the shooting abilities of Undikma petanque athletes. This study uses an experimental method with the "two group pretest posttest design" design. The instrument used for the test of shooting ability is the shooting station number 1, 2, 3, 4, and 5 with a distance of 6 meters, 7 meters, 8 meters and 9 meters. The subjects in this study were Undikma petanque athletes, amounting to 14 people. Samples taken from the results of purposive sampling. Based on the results of t-test analysis showed the same significant results between imagery exercises and without imagery exercises. But imagery training results are better than without imagery exercises seen with the average value of shooting using imagery exercises 4.71 pretest results increased by 13.00. The amount of increase was 8.28. Without imagery training, the initial pretest score of 3.42 increased to 10.00. The amount of increase is 6.57. The difference in the average increase in shooting results with imagery training, and without imagery training is 1.71.